THE EFFECT OF REGIONAL GOVERNMENT REVENUE ON REGIONAL EXPENDITURE OF THE SORONG DISTRICT GOVERNMENT - Pasaribu, Sandi Hasudungan (Penelitian dan Pengembangan Ilmu, 2025)
This study aims to analyze the influence of government revenue on regional expenditure in the Sorong Regency Government. Regional expenditure is an important indicator in the implementation of regional autonomy, reflecting the region's ability to finance various development programs and activities. Government revenue, as the main source of regional funding, plays a crucial role in determining the amount and priority of regional expenditure. The research method used is a quantitative method using secondary data in the form of reports on the realization of the Sorong Regency regional government budget. The results of the study are expected to provide an overview of the extent of the influence of government revenue on regional expenditure in Sorong Regency. These findings can provide input for the regional government in planning and managing the regional budget, as well as in efforts to increase regional revenue to support sustainable development. In addition, this study is also expected to provide scientific contributions in the field of regional finance.